Pengembangan Bahan Ajar Menulis Puisi untuk Siswa di Sekolah Dasar: Sebuah Kajian Research and Development - Awalludin, Awalludin; Nilawijaya, Rita; Novarita, Novarita; Noermanzah, Noermanzah (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
The aims of this study were (1) to describe the results of the analysis of the needs of teachers and students for the development of teaching materials for writing poetry in elementary schools, (2) to describe the results of the prototypes for developing teaching materials for writing poetry for students in elementary schools, and (3) to describe the feasibility teaching materials for writing poetry as a result of development for elementary school students. The type of research used is Research and Development (R & D) with the Jolly and Bolitho models. Data collection techniques in the form of questionnaires and interviews. The data analysis technique is a descriptive analysis technique. The results of the study show that students in elementary schools need poetry writing textbooks related to the content and physical aspects of textbooks. Meanwhile, the teacher was also given a questionnaire to assess teaching materials for writing poetry. Furthermore, the results of expert validation were obtained, namely the appropriateness of the content obtained a score of 21, language obtained a score of 20, presentation obtained a score of 18, and graphics obtained a score of 19. The total score obtained was 78. Based on the results of data analysis, 12 students wanted textbooks that can increase knowledge, 19 students expect teaching materials in the form of textbooks, and 20 students want complete teaching materials. Thus it can be concluded that the prototype of this teaching material is feasible to be used as a poetry writing textbook for students in elementary schools.